Multi-Criteria Assessment of the Development Potential of the Tourism and Recreational Cluster of the Volgograd Region - VLADIMIROVNA, Fetisova Olga; VICTOROVICH, Vladimir Kurchenkov; SERGEEVNA, Matinа Elena (Journal of Environmental Management and Tourism; Vol 6 No 1 (2015): JEMT Volume VI Issue 1(11) Summer 2015, 2016)
The paper formulates a simple methodology for the quantitative assessment of the tourism potential of the region. The study proposes the multi-criteria decision based on the weighted average sum model. This method involves the selection of social and material attributes and their quantitative assessment by means of ranking and scaling. This methodology is applied in the evaluation of the tourism and recreational potential of the Volgograd Region. The major constraints to the development of tourism in certain districts of the region are identified. To optimize the cost of creating tourist infrastructure, the author proposes to adopt the concept of clustering of tourist areas.
Keywords: tourism potential; multi-criteria assessment; recreational cluster; Volgograd; clustering